KETERSEDIAAN DAN PERILAKU KONSUMSI MAKANAN JAJANAN OLAHAN SISWA SEKOLAH DASAR DI BANDAR LAMPUNG - Qurrotun Ayuniyah; Yaktiworo Indriani; Kordiyana K Rangga (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
This research aims to determine the availability of processed snacks in elementary school in Bandar Lampung, students’ decision maker to consume the processed snacks and their consumption behavior, and analyze the differentiation of the students in consuming processed snacks, based on gender and nutritional status. This research is done in Kartika II-5 Elementary school and Rawa Laut 1 Elementary School.  The research data is collected from November 2014-March 2015 by survey method.  The research samples are 57 elementary school student of grade 4 and 13 food merchants.  The data is analyzed by descriptive analysis and Mann Whitney test.  The result showed that the availabilty of the processed snacks based on  nutrition contens  was not available enough.  There were30 kinds processed snacks in Kartika II-5 Elementary School and 15 kinds in Rawa Laut 1 Elementary School, that were available as the main meal and snack food.  The processed snacks made of carbohydrates source as majority of the raw materials, such as rice, flour, tapioca flour, corn and cassava.  The decision maker in consuming processed snacks was the student itself.  The processed snacks that were consumed by the students were mie instan, cireng, siomai, pempek and bakso tusuk.  Iinstant noodle was the most favorite food consumed by the students.  The average consumption frequency of each processed snacks were 3-6 times/month and the eating average per month of instant noodle, “cireng”, “siomai”, “pempek” and “bakso tusuk” were 440.70 grams; 324.21 grams; 1,056.14 grams; 466.67 grams and 137.54 grams respectively.  There was significant difference between the consumption of “siomai” by male and female students.  Male students tended to consume siomai 1,715 times more, than female students. Key words: availability of snack, consumption behavior, processed snack